Poverty Dynamics in Rural Bangladesh - Ahmed, Akhter; Tauseef, Salauddin (2018)
Using two survey rounds from IFPRI's Bangladesh Integrated Household Survey (BIHS), IFPRI researchers from the Bangladesh Policy Research and Strategy Support Program (PRSSP) analyze poverty dynamics between 2011/12 and 2015, as well as offer policy considerations.